Dopamine D2 receptors and alpha1-adrenoceptors synergistically modulate locomotion and behavior of rats in a place avoidance task - Stuchlik, Ales; Petrasek, Tomas; Vales, Karel (Behavioural brain research, 2008)
The processing of spatial information is the focus of interest for many cognitive neuroscientists. Approximately 10 years ago, a novel behavioral paradigm called active allothetic place avoidance (AAPA) was designed allowing the simultaneous assessment of locomotor and spatial behavior. The present study describes the effect of the combined treatment of Long-Evans rats with alpha1-adrenergic and D2 antagonists prazosin (1mg/kg and 2 mg/kg) and sulpiride (10 mg/kg and 30 mg/kg) on locomotion and avoidance behavior in the AAPA task. Results show that co-application of both drugs leads to disturbances in locomotion and avoidance in rats at the doses, which caused no impairments when administered independently. This finding suggests that both types of receptors act synergistically to regulate locomotion and possibly spatial behavior.
Keywords: alfa blokátory; Receptors, Adrenergic, alpha-1; pohybová aktivita; Association Learning; asociační učení; antagonisté dopaminu; sulpirid; interakce mezi receptory a ligandy; prazosin; životní prostředí; prostorové chování; alfa-1-adrenergní receptory; Dose-Response Relationship, Drug; Dopamine Antagonists; Environment; analýza rozptylu; Drug Synergism; Analysis of Variance; krysa rodu Rattus; Avoidance Learning; zvířata; receptory dopaminu D2; Adrenergic alpha-Antagonists; Rats, Long-Evans; synergismus léků; Prazosin; učení vyhýbat se; Male; Sulpiride; potkani Long-Evans; Rats; vztah mezi dávkou a účinkem léčiva; Motor Activity; Animals; Spatial Behavior; mužské pohlaví; Receptor Cross-Talk; Receptors, Dopamine D2